VIOLENCE, DEFORESTATION AND STRUGGLE FOR THE RECOVERY OF GRILLED LANDS IN PONTAL DO PARANAPANEMA: FROM THE DESTRUCTION OF THE INDIGENOUS TERRITORIES TO THE CONSTRUCTION OF A REGION IN DISPUTE OF CLASSES - Feliciano, Carlos Alberto [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2018)
The Pontal do Paranapanema is a disputed territory. This has been the case since its occupation based on indigenous expropriation, land grabbing and deforestation. At present the dispute is in the struggle between the social classes involved in the region. On the one hand we have the land historically taken unduly and illegally, which are under the control of the farmers; on the other hand, lands which have been taken over by a process of struggle and which are under the control of the peasantry, territorialised through rural settlements. There is also a large portion of land in judicial dispute, driven mainly by the pressure of the peasant movements for the State to comply with the determinations that the law competes to it, that is, to discriminate and to reclaim the lands that are of public patrimony. Only with the actions of social movements through land occupations, especially in the mid-1990s, did the State seek to redefine the allocation of public lands. The agreements made between the state and the farmers allowed both the ( re) production of the peasantry, in the form of rural settlements, and the farmers by indemnifying improvements that became close to the market price, thus enabling the purchase of land for other regions The text shows current data on the discriminatory lawsuits and the positioning of the Sao Paulo government by failing to retake the more than 60,000 hectares of land already considered as vacant lands, thus legitimizing an illegal practice of land grabbing to the detriment of the resumption and creation of rural settlements.
Keywords: landless; conflict; grilagem; Pontal do Paranapanema; public lands